UK trainee-led paediatric governance collaboratives: improving the lives of both trainees and children. Issue 2 (9th May 2019) - McDermott, Helen; Vawda, Hannah; Harvey, Kate Christina; Lloyd, Siwan; Course, Christopher William; Broomfield, Rebecca; Greenwood, Annabel; Mason, Timothy; Kirk, Jeremy
Abstract : Research is vital to paediatrics; however, many trainees feel there is a deficit in their opportunities, experience and exposure in this area. Three training regions in the UK, the West Midlands, Wales and Peninsula, have recently started region-wide, trainee-led research and governance collaboratives aimed at improving trainee access and education in research, undertaking good quality, multicentre audit, quality improvement and pilot projects in collaboration across the regions and implementing change. We report on the experiences, benefits and challenges of these trainee collaboratives (Paediatric Research Across the Midlands, Wales Research and Education Network and Peninsula Trainee Research Audit and Innovation Network) including a trainee survey looking at how these initiatives have improved skills in conducting multicentre prospective studies, team working skills, leadership, understanding of statistics and manuscripts and presentation skills. We also describe how collaboration with colleagues and participation in projects can benefit trainees in a wider sense of purpose and help to encourage morale, as well as what can be learnt as paediatric training moves forward.